Peroxisome proliferator-activated receptor gamma co-activator-1 alpha in depression and the response to electroconvulsive therapy. Issue 11 (7th September 2018) - Ryan, Karen M.; Patterson, Ian; McLoughlin, Declan M.
Abstract: Background: The transcriptional coactivator peroxisome proliferator-activated receptor- γ coactivator (PGC-1 α ), termed the 'master regulator of mitochondrial biogenesis', has been implicated in stress and resilience to stress-induced depressive-like behaviours in animal models. However, there has been no study conducted to date to examine PGC-1 α levels in patients with depression or in response to antidepressant treatment. Our aim was to assess PGC-1α mRNA levels in blood from healthy controls and patients with depression pre-/post-electroconvulsive therapy (ECT), and to examine the relationship between blood PGC-1α mRNA levels and clinical symptoms and outcomes with ECT. Methods: Whole blood PGC-1α mRNA levels were analysed in samples from 67 patients with a major depressive episode and 70 healthy controls, and in patient samples following a course of ECT using quantitative real-time polymerase chain reaction (qRT-PCR). Exploratory subgroup correlational analyses were carried out to determine the relationship between PGC-1α and mood scores. Results: PGC-1α levels were lower in patients with depression compared with healthy controls ( p = 0.03). This lower level was predominantly accounted for by patients with psychotic unipolar depression ( p = 0.004). ECT did not alter PGC-1α levels in the depressed group as a whole, though exploratory analyses revealed a significant increase in PGC-1α in patients with psychotic unipolar depression post-ECT ( p = 0.045). We found no relationship between PGC-1α mRNA levels and depression severity or the clinical response to ECT. Conclusions: PGC-1 α may represent a novel therapeutic target for the treatment of depression, and be a common link between various pathophysiological processes implicated in depression.